2017
DOI: 10.3847/1538-4357/aa5be5
|View full text |Cite
|
Sign up to set email alerts
|

How AGN and SN Feedback Affect Mass Transport and Black Hole Growth in High-redshift Galaxies

Abstract: By using cosmological hydrodynamical simulations we study the effect of supernova (SN) and active galactic nuclei (AGN) feedback on the mass transport of gas on to galactic nuclei and the black hole (BH) growth down to redshift z ∼ 6. We study the BH growth in relation with the mass transport processes associated with gravity and pressure torques, and how they are modified by feedback. Cosmological gas funelled through cold flows reaches the galactic outer region close to free-fall. Then torques associated to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 67 publications
11
37
1
Order By: Relevance
“…At this point, because of the larger energy injection powered by accretion, the gas around the MBH is heated up to more than 10 6 K and the growth slows down, with an average accretion rate oscillating between 0.5 and 0.8 times the Eddington limit, and the MBH reaches M BH = 8.6 × 10 8 M by z ≈ 7. The behaviour observed for the MBH growth is consistent with several previous studies (Dubois et al 2014c;Habouzit et al 2017;Prieto et al 2017;Anglés-Alcázar et al 2017), where the MBH was found to starve until the galaxy reached a critical mass between 10 9 M and 10 10 M , or a halo mass/temperature about 10 11 −10 12 and 10 5.6 K (Bower et al 2017;McAlpine et al 2018). This result implies that our initial seed mass (see Section 2.2.1) is not crucial for the MBH evolution, which is instead regulated by the galaxy's Gas Stars 10 11 10 10 10 9 10 8 10 7 Σ gas (M ⊙ kpc −2 ) 10 11 10 10 10 9 10 8 10 7 Σ gas (M ⊙ kpc −2 ) 10 10 10 9 10 8 10 7 ability to funnel gas towards the centre.…”
Section: The Central Mbhsupporting
confidence: 91%
See 1 more Smart Citation
“…At this point, because of the larger energy injection powered by accretion, the gas around the MBH is heated up to more than 10 6 K and the growth slows down, with an average accretion rate oscillating between 0.5 and 0.8 times the Eddington limit, and the MBH reaches M BH = 8.6 × 10 8 M by z ≈ 7. The behaviour observed for the MBH growth is consistent with several previous studies (Dubois et al 2014c;Habouzit et al 2017;Prieto et al 2017;Anglés-Alcázar et al 2017), where the MBH was found to starve until the galaxy reached a critical mass between 10 9 M and 10 10 M , or a halo mass/temperature about 10 11 −10 12 and 10 5.6 K (Bower et al 2017;McAlpine et al 2018). This result implies that our initial seed mass (see Section 2.2.1) is not crucial for the MBH evolution, which is instead regulated by the galaxy's Gas Stars 10 11 10 10 10 9 10 8 10 7 Σ gas (M ⊙ kpc −2 ) 10 11 10 10 10 9 10 8 10 7 Σ gas (M ⊙ kpc −2 ) 10 10 10 9 10 8 10 7 ability to funnel gas towards the centre.…”
Section: The Central Mbhsupporting
confidence: 91%
“…This work was granted access to the High Performance Computing resources of CINES under the allocations A0020406955, and A0040406955 by GENCI, and it has made use of the Horizon Cluster, hosted by Institut d'Astrophysique de Paris, for the analysis of the simulation results. The maps reported in this work have been created using pynbody (Pontzen et al 2013).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…We allowed for up to eight additional refinement levels (l max = 18); however the highest refinement level reached by z = 7 was l = 15 resulting in a best physical resolution of 64.5 pc. We did not model black holes (BHs), since their feedback is likely not important for high-redshift galaxy evolution (Scannapieco & Oh 2004;Somerville et al 2008;Jeon et al 2012;Prieto et al 2017), the galaxy mass range explored or for the parameters we are interested in investigating. The redshift of reionization was also a free parameter, which we set to z re = 8.5, as reported by the Planck Collaboration et al (2016).…”
Section: Simulation Setupmentioning
confidence: 99%
“…Their results are generally in agreement with our simulation, although their numerical validation through the EAGLE simulation does not follow BH and galaxy growth to masses as low as ours. Prieto et al (2017) perform a detailed comparison between the influence and interaction of SN and AGN feedback, aimed specifically at low mass galaxies in the high-redshift Universe. This study in complementary to ours in that we analyse the effect of feedback on a population of BHs, while Prieto et al (2017) focus on the physical interactions, but on only one galaxy in a zoom.…”
Section: (7)mentioning
confidence: 99%